1997
DOI: 10.1021/la9702289
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/Surfactant Complexes at the Air/Water Interface Detected by a Simple Measure of Surface Viscoelasticity

Abstract: The rheology of the air/water interface of mixed polymer/surfactant systems has been examined by the talc particle test. Polymer/surfactant pairs studied range from strongly interacting polyelectrolytes/ oppositely charged surfactant systems, such as sodium hyaluronate/alkyltrimethylammonium halides, carboxymethylcellulose/hexadecyltrimethylammonium chloride (HTAC), and an alternating copolymer of acrylamide and diallyldimethylammonium chloride (Merquat-550)/sodium dodecyl sulfate (SDS) to less strongly intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 19 publications
7
35
0
1
Order By: Relevance
“…At ratios close to 1, Monteux et al 73 observed very hydrophobic complexes in their surface tension measurements for the C 12 TAB/PSS system. These findings are supported by surface rheology studies [74][75][76][77] where the surface shows high elasticity which indicates a large amount of material at the interface. It was even proposed that surface tension is just a question of polymer/surfactant ratio 69 due to the fact that the surface tension was constant when plotted versus the ratio.…”
Section: Effect On Film Thicknesssupporting
confidence: 65%
“…At ratios close to 1, Monteux et al 73 observed very hydrophobic complexes in their surface tension measurements for the C 12 TAB/PSS system. These findings are supported by surface rheology studies [74][75][76][77] where the surface shows high elasticity which indicates a large amount of material at the interface. It was even proposed that surface tension is just a question of polymer/surfactant ratio 69 due to the fact that the surface tension was constant when plotted versus the ratio.…”
Section: Effect On Film Thicknesssupporting
confidence: 65%
“…The band at 1573–1560 cm −1 was attributed to the COO asymmetrical stretching of COO groups, and that at 1460–1408 cm −1 was attributed to the COO symmetrical stretching of COO groups. Bands resulting from CH 2  symmetric stretching vibrations were observed in the case of the surfactant‐added samples at 2845–2830 cm −1 ; this verified the presence of surfactant molecules . Sample N had no new peak at 2845–2830 cm −1 .…”
Section: Resultssupporting
confidence: 51%
“…Excellent reviews on the same subjects have been issued by Goddard and co-workers [42][43][44], by Lindman and coworkers [45,46], and in specialized books [47][48][49]. It is not easy to avoid partial overlapping of the subjects reported here with the above contributions.…”
Section: Introductionmentioning
confidence: 92%